THE ECONOMIC AND SOCIAL SIGNIFICANCE OF KARAKALPAKSTAN'S AVIATION SECTOR DURING THE YEARS OF INDEPENDENCE - Qitaybekov Azizbek (Web of Journals Publishing, 2025)
This article discusses the development of Karakalpakstan's air transport sector during the years of independence, the opening of new air routes, and the arrival of new aircraft.
Keywords: Airport, plane, Boeing-310, Uzbekistan Airways, Nukus, independence, TU-154.